Non catheter-related bacteremia caused by Pseudomonas oryzihabitans in an adolescent with chronic renal failure undergoing peritoneal dialysis - Karampatakis, T (SOCIETY OF "FRIENDS OF HIPPOKRATIA JOURNAL", 2012)
A Pseudomonas oryzihabitans clinical isolate was recovered from a blood sample. The patient, a 14-year-old-adolescent underwent parathyroidectomy due to secondary hyperparathyroidism. The patient had been going peritoneal dialysis because of chronic renal failure. According to the susceptibility testing conducted with phenotypic methods the microorganism was sensitive to the vast majority of the antibiotics. The isolation of this rare species of Pseudomonas combined with the patient's medical history stimulated as to focus on the causes of the bacteremia, which was non catheter-related.